Roots of democratic education in the Philippines - Lacuesta, Manuel Gascon (Education Quarterly, 1958)
From the beginning, the American government in the Philippines was committees to the concepts of good government and democratic self-government for the people; hence, it inaugurated early the policy of giving the people, practical education in the art and science of self-government. A democratic form of government is successful only in so far as the people who compose it are enlightened to the degree of being able to exercise their capacity of self-government for the benefit of all the members of society. Because of the general awakening, the Filipinos became more critical of what the schools were doing; this critical attitude spurred the schools to exert more efforts to improve their work in order to give the people more substantial benefits. Of all the institutions established by the Americans in the Philippines, the schools followed less their Spanish precedents and more the American educational institutions.